2019
DOI: 10.11648/j.ijhpebs.20190501.16
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status Disclosure to Sexual Partner(s) and Associated Factors Among Young Adults, A Mixed Methods Study

Abstract: With a documented HIV prevalence among adults of 12.6% with disparities by sex; 15.7% and 9.3% among women and men respectively, Namibia is one of the first countries reported to be nearing epidemic control for HIV. Namibia has been very successful in ensuring universal treatment access for people living with HIV. For prevention interventions, the importance of HIV status disclosure among HIV-infected individuals, particularly to their sexual partners cannot be over emphasized. We used a mixed methods approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The likelihood of disclosing HIV positive status to sexual partner was more among counseled adult HIV infected peoples than not. The report of a study conducted in Namibia showed that ever had HIV counseling positively associated with HIV disclosure [60]. It was also in…”
Section: Discussionmentioning
confidence: 96%
“…The likelihood of disclosing HIV positive status to sexual partner was more among counseled adult HIV infected peoples than not. The report of a study conducted in Namibia showed that ever had HIV counseling positively associated with HIV disclosure [60]. It was also in…”
Section: Discussionmentioning
confidence: 96%